2018
DOI: 10.18823/asiatefl.2018.15.1.19.242
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers' Progressive Reflective Practices Using Weekly Journals in an Action Research Project

Abstract: In general, action research refers to any systematic inquiry conducted by teacher researchers or other stakeholders in the teaching/learning environment to gather information about how teachers teach and how well their students learn (Mills, 2011). By being involved in action research, teachers can experience the opportunities for reflection to observe, evaluate, and reflect systematically on their classroom practices in order to promote understanding and self-awareness and to make changes when necessary (McDo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In relation to the first aspect of the research, the results portrayed that the teachers applied reflective practice to adjust and make changes to plan the lesson, during teaching and after teaching to reframe their teaching for future lesson [9,36,45]. Similar to Sua, et al [17] as well as Lee [36], the teachers in this study claimed that reflective activities support them to be more progressive and enable them to increase their teaching quality [2][3][4][5] but, the findings showed that, rather than practicing reflective practice on their own, the teachers need ample support from the school administration to improve their practices in schools [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In relation to the first aspect of the research, the results portrayed that the teachers applied reflective practice to adjust and make changes to plan the lesson, during teaching and after teaching to reframe their teaching for future lesson [9,36,45]. Similar to Sua, et al [17] as well as Lee [36], the teachers in this study claimed that reflective activities support them to be more progressive and enable them to increase their teaching quality [2][3][4][5] but, the findings showed that, rather than practicing reflective practice on their own, the teachers need ample support from the school administration to improve their practices in schools [17].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the first aspect of the research, the results portrayed that the teachers applied reflective practice to adjust and make changes to plan the lesson, during teaching and after teaching to reframe their teaching for future lesson [9,36,45]. Similar to Sua, et al [17] as well as Lee [36], the teachers in this study claimed that reflective activities support them to be more progressive and enable them to increase their teaching quality [2][3][4][5] but, the findings showed that, rather than practicing reflective practice on their own, the teachers need ample support from the school administration to improve their practices in schools [17]. The support and collaborative reflective activities [23] will motivate the teachers in implementing reflective activities in their teaching and learning process which could ease the teachers' stress in providing effective teaching [5,43] to increase students' learning performance and to fulfil the pedagogical, content and context demands [5,14] based on their own pace and significant to the context as suggested by Jejo and Haji [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation